Persuasi dalam Wacana Iklan - Sri Puji Astuti (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2017)
Advertisement is a marketing tool that helps selling goods, providing services, and ideas through certain way in the form of persuasive information. How the persuasion strategy used the advertiser in other to be able to draw attention of potential customers is discussed in this paper. This research data is in the form of advertising discourse. The data used in this study comes from the advertising discourse of online. In the data collection activities used was the observation method or refer method namely listening the use of language in the advertising discourse online. Data was selected according to the research needs. Data were analyzed by using content analysis. The results showed that there were two ways of advertisers persuading prospective customers was persuasion implicitly, and explicitly.